BEGINNING TEACHERS AS EFFECTIVE CLASSROOM MANAGERS: HOW ARE THEY? ... MANAGING? - Ralph, Edwin G. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1994)
The results of a survey of the self-reported classroom management practices of 151 beginning teachers confirmed what previous research has repeatedly reported: (a) that classroom management is vitally connected to effective teaching/learning; (b) that novice teachers often find management to be challenging and/or difficult; and (c) that they could have been better prepared to meet this challenge had the typical "theory practice" gap between their preservice practicum and their first-year(s) teaching been reduced. The author suggests ways to improve this link "between practicum and practice," by means of a supervisory framework emphasizing the contextual and developmental nature of effective teaching/learning. RÉSUMÉ Les résultats d’une enquête sur les pratiques de gestion de classe rapportées par 151 enseignants débutants confirment les résultats des recherches antérieures: a) la gestion de classe est étroitement liée à l’efficacité des enseignements/apprentissages; b) les enseignants néophytes considèrent souvent la gestion de classe comme un défi et(ou) une difficulté et c) la préparation à relever ce défi aurait été meilleure si le fossé typique "théorie-pratique" entre leur stage et leurs premières années d’enseignement avait été réduit. L’auteur propose des moyens pour améliorer le rapport entre la théorie et la pratique, notamment un cadre directeur axé sur la nature contextuelle et développementale des enseignements/apprentissages efficaces.